The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1002/pd.1970110305
|View full text |Cite
|
Sign up to set email alerts
|

Further predictors of renal dysplasia in fetal obstructive uropathy: Bladder pressure and biochemistry of ‘fresh’ urine

Abstract: Urine was aspirated on two consecutive days from the dilated bladder of nine fetuses with lower urinary tract obstruction. Gestational age ranged from 17 to 35 weeks. Renal dysplasia was diagnosed histologically in four fetuses, whereas the other five had normal renal histology or only partial dysplasia. Urinary sodium (Na+) and osmolality (Osm) decreased significantly in the second urine sample 1 day after bladder emptying (median decrease: Na+ = -11.3 per cent; Osm = -13.3 per cent). Although there were no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…Ten patients (71%) had at least one VAS. When compared to similar previous studies, where 46%-56% of patients had shunts placed, we had a significantly higher percentage of patients that underwent VAS [9,[19][20][21]. This likely reflects the increasing popularity of the technique over the past decade and specific intervention-based referral patterns for our center.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Ten patients (71%) had at least one VAS. When compared to similar previous studies, where 46%-56% of patients had shunts placed, we had a significantly higher percentage of patients that underwent VAS [9,[19][20][21]. This likely reflects the increasing popularity of the technique over the past decade and specific intervention-based referral patterns for our center.…”
Section: Discussionmentioning
confidence: 49%
“…In the present study we identified 14 patients prenatally diagnosed with LUTO over an 8-year period, all of whom were male with normal karyotypes and variable ultrasound features classic for the condition [9,[16][17][18][19][20][21]. Ten patients (71%) had at least one VAS.…”
Section: Discussionmentioning
confidence: 96%
“…They attributed the differences in morpholo gy primarily to ectopic origins of the ureteric bud from the wolffian duct. Nicolini et al [ 12] reached a similar conclusion and pointed out that renal dysplasia might be an association rather than a consequence of obstruction.…”
Section: Discussionmentioning
confidence: 56%
“…Nicolini et al [34] were the first to suggest that predictive accuracy may be improved by a second vesicocentesis in order to obtain "fresh" urine after the initial bladder drainage. Johnson et al [35] later expanded this to a series of three sequential fetal bladder aspirations, each 48 h apart.…”
Section: Sequential Urine Analysismentioning
confidence: 99%